(untitled) (Academic Journal of Internal Affairs, 2016)
This author argues in favour of introducing comprehensive solutions at the EU level concerning the institutional protection of stateless persons in the area of freedom, security and justice, including the elaboration of a legal framework which would be applicable for the establishment of Member States’ practices and statelessness determination procedures.